Al-Ijtihād Al-Maqāṣidī Dalam Perspektif: Ontologi, Epistemologi, Dan Aksiologi - Baso Muhammad Nibras Abiyyu; Fatmawati; Abd Rauf Muhammad Amin (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
The development of modern society characterized by technological advances, globalization, and the emergence of various new problems in the economic, social, political, health, and environmental fields demands renewal in the development of Islamic law. In this context, al-ijtihād al-maqāṣidī is present as a relevant approach to answer contemporary legal challenges while remaining based on sharia principles. This study aims to analyze the concept, position, and role of al-ijtihād al-maqāṣidī in the development of contemporary Islamic law. The research method used is normative legal research with a qualitative approach and library research. Data were obtained from primary and secondary sources related to maqāṣid al-shari'ah, ushul fiqh, and contemporary ijtihad studies. The research results show that al-ijtihād al-maqāṣidī is a method of establishing law oriented towards the realization of the objectives of sharia through consideration of the benefit (jalb al-maṣāliḥ) and the prevention of harm (dar’ al-mafāsid). This approach not only emphasizes textual understanding of the texts, but also considers wisdom, the value of justice, and evolving social realities. Thus, al-ijtihād al-maqāṣidī is able to become a methodological instrument that bridges religious texts and the needs of modern society so that Islamic law remains adaptive, relevant, and oriented towards the benefit of the community.